COVID-19 policies and hoteliers' responses in Japan - Hiroyuki Fukuchi; Wataru Uehara; Hiromi Kamata; Geer He (Annals of Tourism Research Empirical Insights, 2022)
This study aims to identify the hoteliers' crisis management practices during COVID-19 and analyse the relationship between each practice and government policy. Through in-depth interviews with five hotel chains, common crisis management practice patterns, factors that lead to differences in crisis management practices and the influences of policies on these practices were identified. The findings show strong and complicated relationships between policy and hoteliers' crisis management practices. Although many crisis management practices were encouraged by the government, some practices were not influenced by the policy and others were indirectly impeded. Hoteliers are not only passively affected by government policies, but respond actively to them as well as demonstrate their own initiative in response to the crisis.
Keywords: 330; COVID-19 pandemic; Hoteliers' responses; Crisis management; Self-restraint; Economic stimulation